User Resistance: Reasons MSME Actors Are Hesitant to Prepare Financial Reports in Siak Regency - Anita, Nur; Maulana, Hutomo Atman; Eriska, Ririn; Lusiana, Sonia (Politeknik Negeri Bengkalis, 2024)
The study aims to investigate the impact of perceived value, switching cost, switching benefits, and self-efficacyfor change on user resistance in preparing financial reports in MSMEs. The hypothesis was tested empirically with a sampleof 63 MSME actors from Siak Regency, Riau Province. This study uses structural equation modeling with WarpPLS 7.0as a test tool. The study's findings suggest that MSME actors may be resistant to preparing financial statements becausethey are worried about the expenses they will spend and forfeit if they do so. They believe that if they adopt new proceduresand guidelines, all their earlier work will have been in useless. Furthermore, the study's findings demonstrate that whileMSME actors exhibit strong self-confidence in adapting to change when it is viewed to have a good effect, resistance willpersist if the costs and sacrifices associated with adjusting to new circumstances are as substantial. This study contributesby providing empirical data on the elements that lead to user resistance when creating financial reports. Practically, thisstudy shows that it is important for the government and policymakers to pay attention to the factors that cause MSMEs torefuse to prepare financial reports so that these factors can be mitigated, and the objectives of financial reporting can beachieved.